2008
DOI: 10.1002/mds.21775
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of sham surgery: Perspective of patients

Abstract: Sham surgery is used as a control condition in neurosurgical clinical trials in Parkinson's disease (PD) but remains controversial. This study aimed to assess the perspective of patients with PD and the general public on the use of sham surgery controls. We surveyed consecutive patients from a university-based neurology outpatient clinic and a community-based general internal medicine practice. Background information was provided regarding PD and two possible methods of testing the efficacy of a novel gene tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…A majority (97%) of PD clinical researchers believe sham surgery controls are better that unblinded controls for testing the efficacy of neurosurgical interventions (4). Others argue that sham surgery is a public health concern as vulnerable individuals are exposed to surgical procedures that have no benefits (6). The ALS community can learn from the experience of the PD community when fetal stem cell treatment was under consideration.…”
Section: Discussionmentioning
confidence: 97%
“…A majority (97%) of PD clinical researchers believe sham surgery controls are better that unblinded controls for testing the efficacy of neurosurgical interventions (4). Others argue that sham surgery is a public health concern as vulnerable individuals are exposed to surgical procedures that have no benefits (6). The ALS community can learn from the experience of the PD community when fetal stem cell treatment was under consideration.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, recruitment of a suspected INPH patient into a conservative arm might be diffi cult. Doing a sham (placebo) surgery or simply randomizing patients to ligated or open shunt tube groups is controversial from an ethical point of view, since patients with a nonfunctioning shunt will be subjected to unnecessary surgery, with its potential complications and with no personal benefi t; again, recruitment into such a trial could prove to be a challenge [ 2,5,7,8,11,13 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of subjects selecting nonparticipation was in the PD group (34%, while in the other two the maximum nonparticipation portion accounted for 10.4%). Also, the PD group of subjects was the least willing one to be involved in a blinded study (24.5%, while the other groups favored this option in a percent from 35 to 40%) [24]. The authors concluded that “patients with PD, when compared with patients with non-PD neurology or primary care, may have adapted to their chronic illness and may not be so desperate that they would be more eager to participate in risky research.…”
Section: Discussionmentioning
confidence: 99%